CRISPR/Cas9 editing in human pluripotent stem cell-cardiomyocytes highlights arrhythmias, hypocontractility, and energy depletion as potential therapeutic targets for hypertrophic cardiomyopathy - Mosqueira, Diogo; Mannhardt, Ingra; Bhagwan, Jamie R.; Lis-Slimak, Katarzyna; Katili, Puspita; Scott, Elizabeth; Hassan, Mustafa; Prondzynski, Maksymilian; Harmer, Stephen C.; Tinker, Andrew; Smith, James G.W.; Carrier, Lucie; et al. (Oxford University Press, 2018)
Aims: Sarcomeric gene mutations frequently underlie hypertrophic cardiomyopathy (HCM), a prevalent and complex condition leading to left ventricle thickening and heart dysfunction. We evaluated isogenic genome-edited human pluripotent stem cell-cardiomyocytes (hPSC-CM) for their validity to model, and add clarity to, HCM. Methods and results: CRISPR/Cas9 editing produced 11 variants of the HCM-causing mutation c.C9123T-MYH7 (p.R453C-βMHC) in 3 independent hPSC lines. Isogenic sets were differentiated to hPSC-CMs for high-throughput, non-subjective molecular and functional assessment using 12 approaches in 2D monolayers and/or 3D engineered heart tissues. Although immature, edited hPSC-CMs exhibited the main hallmarks of HCM (hypertrophy, multi-nucleation, hypertrophic marker expression, sarcomeric disarray). Functional evaluation supported the energy depletion model due to higher metabolic respiration activity, accompanied by abnormalities in calcium handling, arrhythmias and contraction force. Partial phenotypic rescue was achieved with ranolazine but not omecamtiv mecarbil, while RNAseq highlighted potentially novel molecular targets. Conclusion: Our holistic and comprehensive approach showed that energy depletion affected core cardiomyocyte functionality. The engineered R453C-βMHC-mutation triggered compensatory responses in hPSC-CMs, causing increased ATP production and αMHC to energy-efficient βMHC switching. We showed that pharmacological rescue of arrhythmias was possible, while MHY7:MYH6 and mutant:wild-type MYH7 ratios may be diagnostic, and previously undescribed lncRNAs and gene modifiers are suggestive of new mechanisms.